Examining the herding behavior in Chinese Stock Market - Xu, Yan (2006)
Herding behaviour is the elusive phenomena. It means collective actions behaved by individuals under uncertain conditions (Adler and Adler 1984). Whereas the current financial market has an important character which is its uncertainty and fuzziness. Hence, investors sometimes have conformity in mind. This has already illuminated in the earlier economic theory. Keynes (1936) reckons that long-term investors probably are not willing to make decision based on their private information and own opinions because they want to avoid being considered as imprudence and not tallying with conventionality. As he mentioned in this paper, that the failure according with tradition can bring more benefits to reputation than success which is not according with tradition.